Pharmacological properties of ginger (Zingiber officinale): what do meta-analyses say? a systematic review - Paudel, Keshab Raj; Orent, Jake; Penela, Olivia Grace (Frontiers in Pharmacology, 2025)
This review evaluates findings from meta-analyses on the pharmacological effects of ginger (Zingiber officinale), focusing on inflammation, type 2 diabetes mellitus (T2DM), oxidative stress, and pregnancy-associated nausea and vomiting (NVP). A systematic PubMed search identified relevant meta-analyses published between 2010 and 2025. Ginger supplementation was associated with significant reductions in circulating C-reactive protein (CRP), high-sensitivity CRP, and tumor necrosis factor-α, indicating anti-inflammatory activity. In patients with T2DM, ginger significantly lowered glycosylated hemoglobin 1c and fasting blood glucose. Furthermore, antioxidant effects were observed through reduced malondialdehyde levels and increased glutathione peroxidase activity. In pregnant women, ginger significantly alleviated nausea symptoms but had no significant effect on vomiting frequency. Doses of 1–3 g daily were commonly used for anti-inflammatory, antioxidant, and antidiabetic purposes, while 500–1,500 mg daily in divided doses was used for NVP. Belching was identified as a potential side effect in pregnant women. Despite encouraging outcomes, high heterogeneity in one metanalysis (I2 = 98.1%) and potential risk of bias in ‘blinding’ and ‘other bias’ categories across studies reported by another metanalysis highlight the need for further high-quality large-scale randomized controlled trials and meta-analyses to confirm the clinical benefits of ginger.